Untargeted metabolomic and transcriptomic analysis in spring and durum wheat reveals potential mechanisms associated with the early stem solidness phenotype and resistance to wheat stem sawfly - Hager, Megan S.; Cook, Jason P.; Bothner, Brian; Weaver, David K. (Frontiers in Plant Science, 2025)
Wheat stem sawfly (WSS) causes devastating yield loss in both common bread wheat (Triticum aestivum L.) and durum wheat (Triticum turgidum L. var durum) in the North American Great Plains. The early stem solidness phenotype confers solid stems early in plant development coinciding with the flight period of WSS and provides protection to plants during the critical oviposition period. With this phenotype, pith is lost as the plant develops, which may allow for enhanced biological control of surviving larvae by braconid parasitoids Bracon cephi (Gahan) and Bracon lissogaster Muesebeck, as well as having additional potential yield benefits from utilizing reabsorbed pith components. Here, we use an untargeted transcriptomics and metabolomics approach to explore the mechanisms related to the early stem solidness phenotype in three cultivars of spring wheat and two cultivars of durum wheat in addition to three near- isogenic pairs of spring wheat and two near- isogenic pairs of durum wheat. We identified effects of growth stage and allele on expression of metabolites and transcripts associated with stem solidness, development of cell walls and programmed cell death. A caffeic acid methylesterase and pectin methylesterase were upregulated in hollow stemmed Reeder and lines with the 3BLa allele, which likely influences lignin subunit proportions as well as the production of volatile semiochemicals that impact the behavior of adult WSS. TaVPE3cB, a gene associated with programmed cell death and thickening of cell walls, also had increased expression in hollow stemmed lines and is likely partially responsible for the hollow stemmed phenotype observed. Growth stage and allele also affected the expression of transcripts and metabolites involved in the phenylpropanoid pathway, carbohydrate and glycoside biosynthesis and lipid biosynthesis, implicating the involvement of these pathways in resistance and plant response to infestation by WSS.